2007
DOI: 10.2337/db06-0267
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Inhibits Acyl-CoA Synthetase Activity and Fatty Acid Partitioning to Diacylglycerol and Triacylglycerol via a Peroxisome Proliferator–Activated Receptor-γ–Independent Mechanism in Human Arterial Smooth Muscle Cells and Macrophages

Abstract: Rosiglitazone is an insulin-sensitizing agent that has recently been shown to exert beneficial effects on atherosclerosis. In addition to peroxisome proliferator-activated receptor (PPAR)-␥, rosiglitazone can affect other targets, such as directly inhibiting recombinant long-chain acylCoA synthetase (ACSL)-4 activity. Because it is unknown if ACSL4 is expressed in vascular cells involved in atherosclerosis, we investigated the ability of rosiglitazone to inhibit ACSL activity and fatty acid partitioning in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
79
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 41 publications
7
79
0
Order By: Relevance
“…We have previously shown that ACSL4 is one of the ACSL isoforms expressed in human arterial SMCs ( 17 ). These cells also express ACSL1, ACSL3, and ACSL5 ( 17 ).…”
Section: Acsl4 Sirna Experimentsmentioning
confidence: 99%
“…We have previously shown that ACSL4 is one of the ACSL isoforms expressed in human arterial SMCs ( 17 ). These cells also express ACSL1, ACSL3, and ACSL5 ( 17 ).…”
Section: Acsl4 Sirna Experimentsmentioning
confidence: 99%
“…diacylglycerol (DAG), have been shown to interfere with insulin signaling in skeletal muscle and liver, while in β -cells of pancreas the increased content of ceramide and other lipid metabolites is associated with β -cell apoptosis (Manco et al 2004). FACL4 is involved in de novo synthesis of DAG and FA storage in TG and FACL1 and/or FACL3 have additional effects on FA partitioning into phospholipids (Askari et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Rosiglitazone, which is an insulin-sensitizer, inhibits FACL4 and concomitantly increases activity of stearoyl-CoA desaturase (SCD) and adenosine monophosphate kinase (Evans et al 2004;Boyle et al 2008), was shown to inhibit FA partitioning into DAG and TG in human smooth muscle cells (SMC) and macrophages and only transiently inhibit partitioning of oleic acid into PL in human SMC, through a PPARγ independent mechanism (Askari et al 2007). In only one study, plasma FA in TG after rosiglitazone treatment was assessed in a small group of type 2 diabetics and SCD and Δ 5 but not Δ 6 desaturases activity indexes were increased .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the long-chain acylCoA synthetases for palmitic acid were inhibited by salicylic acid 20,21,25 , diclofenac 20 , ibuprofen 26 , ketoprofen 26 , naproxen 26 , rosiglitazone 27 , thiazolidinediones 28 and troglitazone 29 . Further, arachidonic acid (AA) metabolism in brain has been reported to be a target of valproic acid 30 .…”
Section: Short Communicationmentioning
confidence: 99%